Evaluation of teaching of thinking skills among ESL learners at selected public institutions of higher learning - Syed Aziz Baftim, Sharifah Sheha (2012)
Thinking skills have been implemented in the curriculum of higher learning, however, there is a dearth of studies on the extent to which these skills are infused in the teaching and learning context. Thus, this research is aimed at carrying out an investigation on the infusion of thinking skills among ESL learners of the Pre-diploma and Diploma in Science program in a selected institution of higher learning The objectives of this study is to evaluate the presence of thinking skills and the progression of the use of the thinking skills in the English language courses at the planning, implementation and assessment stages from lower order to higher order thinking from the pre-diploma level to the diploma level in the program. This was a descriptive exploratory study which employed mixed method strategies to collect data, namely interview with the selected lecturers, classroom audio recording and content analysis on related documents for each of the three instructional development stages, namely planning, implementation and assessment stages. The findings show that thinking skills are present in the English language program at all three stages of the Pre-diploma and Diploma in Science program in a selected institution of higher learning. However, more emphasis is given to the inclusion of lower order thinking elements, even though elements of higher order thinking skills are visible. There is a progression in the inclusion of the higher order thinking skills across the subject codes, with some inconsistencies found in relation to the frequency of higher order thinking skills calculated in each of the three stages, especially between the curriculum at the planning stage and other constructs. The incompatibility shows that there is a definite loss in translation to the syllabus that is specifically designed for the teachers to use as a guide and plan for action. Therefore, it is recommended that the infusion of higher order thinking skills in the subjects at the tertiary level is highlighted not only in the curriculum, but also in the actual teaching process and in the assessment of the subject. This will ensure continuous improvement on the curriculum development and guarantee the effectiveness of the programs that are implemented at the tertiary level.